Structural and Functional Characteristics of Color Vision Changes in Choroideremia - Jolly, Jasleen K.; Simunovic, Matthew P.; Dubis, Adam M.; Josan, Amandeep S.; Robson, Anthony G.; Bellini, Marco P.; Bloch, Edward; Georgiadis, Odysseas; da Cruz, Lyndon; Bridge, Holly; MacLaren, Robert E. (Frontiers in Neuroscience, 2021)
Color vision is considered a marker of cone function and its assessment in patients with retinal pathology is complementary to the assessments of spatial vision (best-corrected visual acuity) and contrast detection (perimetry). Rod-cone and chorioretinal dystrophies - such as choroideremia - typically cause alterations to color vision, making its assessment a potential outcome measure in clinical trials. However, clinical evaluation of color vision may be compromised by pathological changes to spatial vision and the visual field. The low vision Cambridge Color Test (lvCCT) was developed specifically to address these latter issues. We used the trivector version of the lvCCT to quantify color discrimination in a cohort of 53 patients with choroideremia. This test enables rapid and precise characterization of color discrimination along protan, deutan and tritan axes more reliably than the historically preferred test for clinical trials, namely the Farnsworth Munsell 100 Hue test. The lvCCT demonstrates that color vision defects - particularly along the tritan axis - are seen early in choroideremia, and that this occurs independent of changes in visual acuity, pattern electroretinography and ellipsoid zone area on OCT. We argue that the selective loss of tritan color discrimination can be explained by our current understanding of the machinery of color vision and the pathophysiology of choroideremia.